The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s12906-017-2043-2
|View full text |Cite
|
Sign up to set email alerts
|

High–efficiency generation of induced pluripotent stem cells from human foreskin fibroblast cells using the Sagunja-tang herbal formula

Abstract: BackgroundSagunja-Tang (SGT-4) is a traditional herbal formula in Korean medicine that is used to treat anti-metabolic syndrome, and has antioxidant activity. In this study, we evaluated the effects of SGT-4 on the formation efficiency of induced pluripotent stem cells (iPSCs) from human foreskin fibroblasts (HFFs) by four reprogramming transcription factors: Oct4, Sox2, KIf4, and c-Myc (OSKM).MethodsSGT-4 contained four different herbal medicines that are composed of Ginseng Radix, Glycyrrhizae Radix et Rhizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…As these residual undifferentiated cells in CPTs are tumorigenic and can form teratomas at ectopic sites after in vivo transplantation, complete differentiation or selective elimination of residual undifferentiated cells in CTPs prior to transplantation is critical for clinical application [5,6]. Several methods for selective removal of undifferentiated iPSCs from a population of differentiated CTPs have been reported, such as modification of cell culture conditions, use of hiPSCs-specific sorting antibodies and chemical inhibitors, and introduction of suicide genes into hiPSCs [7][8][9][10]. However, none of these approaches are clinically applicable for regenerative therapy because of concerns regarding specificity, safety, and cost.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As these residual undifferentiated cells in CPTs are tumorigenic and can form teratomas at ectopic sites after in vivo transplantation, complete differentiation or selective elimination of residual undifferentiated cells in CTPs prior to transplantation is critical for clinical application [5,6]. Several methods for selective removal of undifferentiated iPSCs from a population of differentiated CTPs have been reported, such as modification of cell culture conditions, use of hiPSCs-specific sorting antibodies and chemical inhibitors, and introduction of suicide genes into hiPSCs [7][8][9][10]. However, none of these approaches are clinically applicable for regenerative therapy because of concerns regarding specificity, safety, and cost.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the AMP-activated protein kinase (AMPK) agonist, metformin, which specifically disrupts the cancer stem cell compartment in multiple cancers, limited the tumorigenicity of teratoma-initiating iPSCs without interfering with their pluripotency [35]. Small molecules such as PluriSin#1 (an inhibitor of stearoyl-CoA desaturase), quercetin and YM155 (inhibitors of survivin), dinaciclib (a CDK inhibitor), and cardiac glycosides have been shown to induce selective cell death of undifferentiated iPSCs and efficiently prevent teratoma formation [9,36,37]. However, all of these molecules have been investigated only in preclinical studies, and have not yet been approved for clinical use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human cells reported to have been successfully reprogrammed into EiPSCs include fibroblasts, epithelial cells, keratinocytes, mononuclear cells from adult peripheral blood, cord blood cells, amniotic fluid stem cells, mesenchymal stromal cells, lymphoblasts, lamina propria progenitor cells from oral mucosa, and urothelial cells obtained from urine. A summary of these reported human EiPSC sources is shown in Table 1 8,20,21,32 43,47 52,55,56,58,60 …”
Section: Human Eipsc Sourcesmentioning
confidence: 99%
“…Considerable efforts have been made to improve the efficiency and safety of somatic cellular reprogramming to generate genetically unmodified hiPSCs for clinical applications. Various small molecules, including epigenetic modifiers, metabolic regulators, and antioxidants, and herbal decoction Sagunja-Tang, have been identified that are involved in the reprogramming process and promote the efficiency of iPSC generation [ 13 , 14 , 15 , 16 ]. In particular, chemically induced iPSCs (CiPSCs) can be generated from mouse somatic cells using a combination of seven small molecules, including VC6T (VPA, CHIR99021 a GSK inhibitor, 616452 and Tranylcypromine a monoamine oxidase inhibitor) plus forskolin (a cAMP agonist) and 3-deazaneplanocin A (DZNep, a global histone methylation inhibitor) but not from human cells [ 17 ].…”
Section: Introductionmentioning
confidence: 99%